Network meta‐analysis of Chinese herb injections combined with FOLFOX chemotherapy in the treatment of advanced colorectal cancer. (August 2016) - Ge, L.; Wang, Y‐f.; Tian, J‐h.; Mao, L.; Zhang, J.; Zhang, J‐h.; Shen, X‐p.; Yang, K‐h.
Summary: What is known and Objective: Research has indicated that some Chinese herb injections (CHIs) might be beneficial in combination with chemotherapy, including remedies that might be used as effective chemosensitizers and radiosensitizers, or as palliative therapy. Here, we carried out a network meta‐analysis to assess the clinical efficacy and safety of CHIs combined with oxaliplatin, 5‐fluorouracil and leucovorin (FOLFOX) for advanced colorectal cancer (CRC). Methods: PubMed, EMBASE.com, the Cochrane Central Register of Controlled Trials (CENTRAL), Chinese Biomedical Literature Database (CBM), Wanfang Database and Chinese Journal Full‐text Database were searched from inception to 31 December 2014, to identify relevant randomized controlled trails (RCTs). The risk of bias in included RCTs was evaluated according to the Cochrane Handbook version 5.1.0. Standard pairwise meta‐analysis and Bayesian network meta‐analysis were performed to compare the efficacy and safety of different CHIs combined with FOLFOX. Data were analysed using STATA 12.0 and WinBUGS1.4 software. Results and discussion: We identified 63 eligible studies (with 4837 patients in total), involving 9 CHIs. Pairwise meta‐analysis showed that compared with FOLFOX alone, combinations with Aidi injection and compound matrine injection could significantly improve the overall response rate and quality of life and reduce the incidence of nausea and vomiting (III‐IV), diarrhoea (III–IV), thrombocytopenia (III–IV), leukopenia (III–IV) and peripheral neurotoxicity (III–IV). According to results of indirect comparison, there were no statistically significant differences for most of comparison groups. Aidi+FOLFOX, shenqifuzheng+FOLFOX and compound matrine+FOLFOX had the greatest probability of being the best treatment in clinical efficacy and safety, considering the small sample size. What is new and Conclusions: Most of the included studies were of low quality, and there was a scarcity of eligible trials and numbers of participants. Based on currently limited evidence, aidi, shenqifuzheng and compound matrine were superior to other CHIs in patients receiving FOLFOX chemotherapy for advanced CRC. More studies are required to confirm the efficacy of CHIs in combination with FOLFOX for advanced CRC. Abstract : We firstly carried out a network meta‐analysis to assess the clinical efficacy and safety of Chinese herb injections (CHIs) combined oxaliplatin, 5‐fluorouracil and leucovorin (FOLFOX) for advanced colorectal cancer (CRC) to determine which is the best CHIs. We included 63 studies involving 4837 patients. Based on currently limited evidence, aidi, shenqifuzheng and compound matrine were superior to other CHIs in patients of FOLFOX chemotherapy for advanced CRC.